Protein Phosphatase 2A: Role in T Cells and Diseases - Suyasha Roy; Lalit Batra (Journal of Immunology Research)
Protein phosphatase 2A (PP2A) is a serine–threonine phosphatase that plays an important role in the regulation of cell proliferation and signal transduction. The catalytic activity of PP2A is integral in the maintenance of physiological functions which gets severely impaired in its absence. PP2A plays an essential role in the activation, differentiation, and functions of T cells. PP2A suppresses Th1 cell differentiation while promoting Th2 cell differentiation. PP2A fosters Th17 cell differentiation which contributes to the pathogenesis of systemic lupus erythematosus (SLE) by enhancing the transactivation of the Il17 gene. Genetic deletion of PP2A in Tregs disrupts Foxp3 expression due to hyperactivation of mTORC1 signaling which impairs the development and immunosuppressive functions of Tregs. PP2A is important in the induction of Th9 cells and promotes their antitumor functions. PP2A activation has shown to reduce neuroinflammation in a mouse model of experimental autoimmune encephalomyelitis (EAE) and is now used to treat multiple sclerosis (MS) clinically. In this review, we will discuss the structure and functions of PP2A in T cell differentiation and diseases and therapeutic applications of PP2A-mediated immunotherapy.